Wrinkling modelling of space membranes subject to solar radiation pressure - Deng, Xiaowei; Xu, Yixiang; Clarke, Christopher (Composites. Part B, Engineering, 2019)
Large, thin, prestressed membranes known as ‘gossamer’ structures have many applications in space, including light reflection and electromagnetic signal collection. The prestress forces applied to these structures usually causes some wrinkling of the membrane to occur, and the degree of wrinkling affects the reflective performance of the structure. The primary aim was to assess whether solar radiation pressure could affect the wrinkle pattern of gossamer structures, with a particular focus on solar sails. Several prestressed rectangular membranes with dimensions and material properties representative of current and future solar sails, a class of membrane structures typically made of Kapton, were modelled to investigate the effects of pressure on the wrinkle pattern. It was shown that increasing the pressure applied normal to the membrane surface increased the amplitude and decreased the wavelength of the wrinkles. However, no significant change in the wrinkle pattern was found to occur until the magnitude of the applied pressure was much greater than that likely to be experienced by gossamer structures due to solar radiation pressure. Therefore it was concluded that the effects of solar pressure will have no significant impact on the future development of larger and thinner gossamer structures than exist at present.